Shuttle Swim Test for water polo players: validity and reliability - Melchiorri, G.; Manzi, V.; Padua, E.; Sardella, F.; Bonifazi, M. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The purpose of this study, carried out on elite water polo players, was to examine: 1) the relationship between the shuttle swim test (SST) and the performance during official water polo games, and 2) the SST reliability. METHODS: Sixteen male players of the Italian National Water Polo Team (age: 27.9±2.1 years, body mass: 88.5±10.3 kg, height: 186.6±6.9 cm) performed the SST, consisting of two sets of seven repetitions from 40 to 10 m (total of 120 m for each set) at a maximal intensity with 90 s of rest between sets. During the SST, average swimming speed, blood lactate concentration and heart rate were recorded. Direct validity of the SST was evaluated by comparing the average swimming speed with the total distance covered (TD) and the distance covered at high intensity swimming (above 1.8 m/s, HIS) during three official water polo games. SST reliability was assessed by testing the same athletes one week apart. RESULTS:Average swimming speed during the SST was significantly correlated with TD (r=0.67, P<0.01) and HIS (r=0.74, P<0.004). The mean average speed during SST showed high reliability (TE=0.4%; CI 95%: 0.2% to 1.0% ). The T1 vs. T2 difference in mean average speed was not significant. CONCLUSIONS: Present findings demonstrate the validity and reliability of the SST for evaluation of the swimming fitness of water polo players.